A bibliometric analysis of undergraduate thesis submitted to the University of the Philippines Manila-College of Pharmacy Library from 2008-2018 - Bautista, Darren Lambert V. (School of Library and Information Studies, University of the Philippines, Diliman, 2019)
This study used a bibliometric analysis as a collection oriented measure to analyze the citations used in the thesis submitted to the University of the Philippines Manila – College of Pharmacy Library from A. Y. 2008-2018 with a total of 4,819 citations recorded from 183 undergraduate theses of the two program Bachelor of Science in Pharmacy and Bachelor of Science in Industrial Pharmacy.